A 3D flexible microelectrode array for subretinal stimulation - Seo, Hee Won; Kim, Namju; Ahn, Jungryul; Cha, Seongkwang; Goo, Yong Sook; Kim, Sohee (Journal of neural engineering, 2019)
Objective. Various retinal prostheses have been developed to restore the vision for blind patients, and some of them are already in clinical use. In this paper, we present a three-dimensional (3D) microelectrode array for a subretinal device that can effectively stimulate retinal cells. Approach. To investigate the effect of electrode designs on the electric field distribution, we simulated various electrode shapes and sizes using finite element analysis. Based on the simulation results, the 3D microelectrode array was fabricated and evaluated in in vitro condition. Main results. Through the simulation, we verified that an electrode design of square frustum was effective to stimulate with high contrast. Also, the 3D flexible and transparent microelectrode array based on silicon and polydimethylsiloxane was fabricated using micro-electro-mechanical system technologies. In in vitro experiments, the subretinally positioned 3D microelectrodes properly evoked spikes in retinal ganglion cells. The mean threshold current was 7.4 µA and the threshold charge density was 33.64 µC·cm−2 per phase. Significance. The results demonstrate the feasibility of the fabricated 3D microelectrodes as the subretinal prosthesis. The developed microelectrode array would be integrated with the stimulation circuitry and implanted in animals for further in vivo experiments.